Conjoint fMRI method for shortening analysis time - Jarmo Heinonen (Cogent Psychology, 2018)
Neuromarketing objective is to understand the functioning of the human decision-making of the brain. The first neuromarketing research was performed by Read Montague in 2003 and Harper Collins added the word neuromarketing to its dictionary in 2005. The most promising way to perform neuromarketing studies are based on fMRI. The fMRI modality is based on using an MRI scanner to image the change of blood flow in the brain. However, participants cannot stay for long inside the fMRI tube and thus it is necessary to improve on the methodology to shorten the research time. One answer to the problem is the conjoint analysis, that short the time and resulting more attributes to analyze products and services. Conjoint tasks may be viewed as multiattribute decision problems, and conjoint analysis is partly a multiattribute model for measuring consumer attitudes and preferences. Connected conjoint fMRI is very efficient way to analyze neuromarketing studies.